Leadership Effectiveness, Competency Development, and Educational Staff Performance:: Mediating Role of Job Satisfaction and Moderating Role of Digital Literacy - Farid Riadi; Dini Riani (Vifada Management and Social Sciences, 2025)
Purpose: Digital transformation in higher education demands improved performance from educational staff who are adaptable and professional. However, there remains a gap between the demands of digitalisation and the readiness of human resources, particularly in terms of competencies, leadership, and digital literacy. This study aims to analyse the influence of effective leadership, competency development, and digital literacy on the performance of educational staff, both directly and indirectly through job satisfaction, as well as to test the moderating role of digital literacy. Research Design and Methodology: This study employs a quantitative approach using explanatory research methodology. The study population consists of educational staff at private higher education institutions in West Java Province, with a sample size of 100 respondents selected via purposive sampling. Data collection was conducted using a questionnaire with a Likert scale, and data analysis utilised Structural Equation Modelling based on Partial Least Squares (SEM-PLS). The research was conducted between January and March 2025. Findings and Discussion: The results indicate that competency development, effective leadership, and digital literacy play a role in enhancing job satisfaction and the performance of educational staff. Job satisfaction was found to be a key mediating factor in the relationship between organisational variables and performance, whilst digital literacy acts as a moderating factor in this relationship. These findings indicate that improved performance is determined not only by technical factors but also by psychological aspects and the ability to adapt to technology. Implications: The implications of this research emphasise the importance of digital-based competency development strategies, adaptive leadership, and the strengthening of digital literacy to enhance the performance of educational staff in a sustainable manner.